(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Objectives: The study aims to clarify some aspects of social life in the city of Badaun, as it represented an important aspect of the city’s civilized history. With its customs and traditions, because its population is divided between Muslims and Hindus, and each has its own customs and traditions. Methodology: The methodology used in our study is to rely on all the available historical and literary sources, Arabic, Persian, Urdu and English, which requires following the historical approach and focusing on the descriptive and analytical aspects. Hindu and Islamic traditions. The second axis included the custom of sati, which pertains to Indian women, as the people of India used to apply it to widowed women by burning them in order to save them from the shame that might befall them, while the third axis included marriage ceremonies and polygamy. And the fables of Badaun Conclusion: The community was in Badaun with double customs due to the diversity of its population between Muslims and Hindus, so what is permissible for the Hindus is the habit of Sati to burn women, burn the dead, marry young girls, and special ceremonies and rituals for newborns were forbidden to Muslims and some Muslim sultans tried to limit Hindu customs by enacting laws to prevent them, such as Sultan Jalal al-Din Bigger, but did not succeed in reducing them completely.